2015
DOI: 10.1016/j.psyneuen.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Escalation in high fat intake in a binge eating model differentially engages dopamine neurons of the ventral tegmental area and requires ghrelin signaling

Abstract: Please cite this article in press as: Valdivia, S., et al., Escalation in high fat intake in a binge eating model differentially engages dopamine neurons of the ventral tegmental area and requires ghrelin signaling. Psychoneuroendocrinology (2015) and time-limited exposed to a high-fat diet (HFD) display robust binge eating events that gradually escalate over the initial accesses. Intake escalation is proposed to be part of the transition from a controlled to a compulsive or loss of control behavior. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
62
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 51 publications
15
62
2
7
Order By: Relevance
“…The i.c.v.‐injected ghrelin tended to increase HF intake on experimental day 1, and such an increment masked HF intake escalation over the successive days. Furthermore, i.c.v.‐injected LEAP2 1‐14 reduced binge‐like HF intake in a similar fashion to that seen previously in GHSR‐deficient mice . These observations indicate that GHSR activity in the brain affects binge‐like HF intake in mice.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The i.c.v.‐injected ghrelin tended to increase HF intake on experimental day 1, and such an increment masked HF intake escalation over the successive days. Furthermore, i.c.v.‐injected LEAP2 1‐14 reduced binge‐like HF intake in a similar fashion to that seen previously in GHSR‐deficient mice . These observations indicate that GHSR activity in the brain affects binge‐like HF intake in mice.…”
Section: Discussionsupporting
confidence: 81%
“…By contrast to WT mice, GHSR‐deficient mice do not display conditioned place preference for HF diet upon caloric restriction or chronic stress, whereas mice with expression of GHSR selectively in catecholaminergic cells, including the dopamine VTA neurones, show a conditioned place preference for HF diet after chronic stress similar to that seen in WT mice . Previous studies showing that GHSR‐deficient mice exhibit a smaller binge‐like HF intake also reported that these mice display a concomitant reduced activation of the mesolimbic pathway . Thus, it appears reasonable to hypothesise that centrally‐injected GHSR inverse agonists reduce binge‐like HF intake as a result of its action on the mesolimbic pathway.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Animals exposed to a restricted amount of calories from high-fat but not high-sugar diet exhibit decreased attention and increased impulsivity as assessed by 5-choice serial reaction task (5CSRT) **[34] . Limited exposure to a fat source also triggers binge-like eating behavior and increased sensitivity of ML activity, interestingly mice lacking ghrelin-receptor failed to escalate palatable food intake suggesting that energy-related signal such as ghrelin play also a role in ML response to energy-dense food **[35] . y.…”
Section: Introductionmentioning
confidence: 99%